On the 12th Day of Christmas, a Statistician Sent to Me . . . (20th December 2022) - Riley, Richard D; Cole, Tim J; Deeks, Jon; Kirkham, Jamie J; Morris, Julie; Perera, Rafael; Wade, Angie; Collins, Gary S
Abstract : The BMJ's statistical editors relish a quiet Christmas, so make their wish come true and pay attention to the list of common statistical faux pas presented here by Riley and colleagues